(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Contamination of semen with sexually and none sexually transmitted bacteria plays an important role in male infertility, contaminating bacteria should be eradicated by antibiotics, but most of bacteria become resistant to available antibiotics. Therefore most researchers search to find other antibacterial agents. Objective:To evaluate the frequency of bacteria in semen of infertile men and investigate the antibacterial activity of aqueous extract of turmeric (AET) on certain isolated bacteria from semen of infertile men compared with that of doxycycline as a standard antibiotic. Methods:Forty two semen samples obtained from infertile men attending The Higher Institute of Infertility Treatment and Assisted Reproductive Technology were evaluated bacteriologically using standard bacterial culture. Then investigated the antibacterial activity of AET on certain isolated bacteria from semen of infertile men compared with doxycycline using disc diffusion method. Results:Out of 42 semen samples of infertile men, 35(83.03%) were infected with different bacterial species (spp.) accompained with highest incidence rate. The overall frequency of N.gonorrhea and S.epidermides was 8(19%) and for remaining bacterial isolated from semen (S.aureus, G.vaginalis and E.coli) were 6(14.28%). Comparable antibacterial activity of ATE and doxycycline was found to be evident against most isolated bacteria (P